# Yahoo Web Search

related to K.C

1. Sort by

1. ### I need some help with composite functions..i suck at them...?

if K(c)= c+273 - to convert Celsius to kelvin c = K-273 and c(f)= 5/9 ( f-32) to convert Fahrenheit to celsius f = 9c/5 + 32

2 Answers · Science & Mathematics · 16/09/2007

2. ### Find the slope of the line that contains the points named.?

Recall that the slope of the line that contains the points (x₁, y₁) and (x₂, y₂) is: m = (y₂ - y₁)/(x₂ - x₁). Here, we see that: y₂ = c + d, y₁ = c - d, x₂ = c - d, and x₁ = c + d. Therefore, the...

3 Answers · Science & Mathematics · 01/07/2011

3. ### Algebra 2 question. Find k:?

Solving for k from x/k - c/w = y add c/w to both sides x/k = y + c/w x/k = (wy+c)/w cross multiply k(wy+c) = wx divide both sides by (wy+c) k = wx/(wy+c)

1 Answers · Science & Mathematics · 23/01/2013

4. ### Binomial Identity Proof?

Since ∑(from k=0 to n) C(n, k)*C(s, k)k = ∑(from k=0 to n) C(n, n - k)*C... ∑(from k=0 to n) C(n, k)*C(s, k)k = s*C(n+s-1, n-1).

2 Answers · Science & Mathematics · 12/05/2012

5. ### Prove, Disprove or Salvage by Induction, combination problem?

C(n,k) = n!/[k!(n-k)!] C(n,k-1) = n!/[(k-1)!(n-k+1)!] C(n,k) + C(n,k-1) = n!/[k!(n-k)!] + n...n-k+1)n! + k*n!]/[k!(n-k+1)!] = [(n+1)*n!]/[k!(n+1-k)!] = [(n+1)!]/[k!(n+1-k)!] = C(n+1,k)

1 Answers · Science & Mathematics · 11/10/2010

6. ### Algebra 2 word problem ? ?

Just plug 55 in for C k = C + 273 k = 55 + 273 = 328 Kelvin

3 Answers · Science & Mathematics · 25/08/2012

7. ### Finite Math Questions!?

P(X = k) = C*k Therefore, C(1+2+3+4+5+6) = 1. C = 1/21 P(2,4,6) = (2+4+6)/21 = 12/21

1 Answers · Science & Mathematics · 19/01/2013

8. ### Prove that this non-geometric series reduces to this?

...series converge. (Your series has the form ((p^n)/(q^n)) sum_{k=n..oo} (n/k) C(2k, k+n) x^k with x = pq, and with a bit of work one can show that the radius of convergence...

2 Answers · Science & Mathematics · 06/05/2012

9. ### number theory problem help!!?

I will write [c_k c_{k-1} ... c_0]_b for the number whose base-b digit expansion...;= c_j < b for all j, the expression [c_k c_{k-1} .. c_0]_b is defined to be the sum c_k b^k...

1 Answers · Science & Mathematics · 05/09/2011

10. ### Combinatorics question?

C(n,k)C(k,r) = n! / k!(n - k)! * k! / r! (k - r)! = n! (n - k)! r! (k - r)! Do the other one and cancel out (n-r) !, and you find that they are equal.

1 Answers · Science & Mathematics · 11/09/2008